Diagnostic Performance of Positron Emission Tomography/Computed Tomography Using Fluorine-18 Fluorodeoxyglucose in Detecting Locoregional Nodal Involvement in Patients with Anal Canal Cancer: A Systematic Review and Meta-Analysis. (2nd January 2014) - Caldarella, Carmelo; Annunziata, Salvatore; Treglia, Giorgio; Sadeghi, Ramin; Ayati, Narjes; Giovanella, Luca
Abstract : Purpose . The diagnostic performance of positron emission tomography using 18 F-fluorodeoxyglucose (FDG-PET) in detecting nodal involvement in patients with anal canal cancer (ACC) has been investigated by several studies with conflicting results. The aim of our study is to systematically review and meta-analyze published data about this topic. Methods . A comprehensive computer literature search of PubMed/MEDLINE, Scopus, and Embase databases was carried out on July 10 to find relevant articles concerning the diagnostic performance of FDG-PET in detecting locoregional nodal involvement in patients with ACC. No language restriction was used. Pooled diagnostic performance on a lesion-based analysis was calculated. Results . Seven retrospective and five prospective studies have been reviewed. Six studies allowed assessing pooled sensitivity; five studies allowed assessing pooled specificity. Sensitivity and specificity values of FDG-PET/CT on a lesion-based analysis ranged from 31 to 100% and from 53 to 98%, with pooled estimates of 56% (95% CI: 45–67%) and 90% (95% CI: 86–93%), respectively. Conclusions . Our meta-analysis demonstrates that FDG-PET is a specific diagnostic tool in detecting locoregional lymph node involvement in patients with ACC. Low sensitivity is a major concern; however, higher sensitivity could be reached combining FDG-PET with MR scan.